2021
DOI: 10.3390/molecules26092670
|View full text |Cite
|
Sign up to set email alerts
|

Surface Polymers on Multiwalled Carbon Nanotubes for Selective Extraction and Electrochemical Determination of Rhodamine B in Food Samples

Abstract: In this study, we combine magnetic solid phase extraction (MSPE), with the screen-printed carbon electrode (SPCE) modified by a molecular imprinted polymer (MIP) for sensitive and selective extraction and electrochemical determination of Rhodamine B in food samples. A magnetic solid phase extraction (MSPE) was carried out using magnetic poly(styrene-co-divinylbenzene) (PS-DVB) and magnetic nanoparticles (MNPs) synthetized on the surface of multiwalled carbon nanotubes (MWCNTs). An MIP was prepared on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A previous study has shown that the concentration of RhB resulting in a decrease in cell viability was 25 μg/mL, which is equivalent to ∼52 μM . Benmassaoud et al showed a modified SPCE using multiwalled carbon nanotube/TiO 2 that performed a greater sensitivity with an LOD of 0.003 μM of RhB; however, our fabricated sensor’s electrode is still possible to be applied in detecting the presence of RhB in food samples as well.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…A previous study has shown that the concentration of RhB resulting in a decrease in cell viability was 25 μg/mL, which is equivalent to ∼52 μM . Benmassaoud et al showed a modified SPCE using multiwalled carbon nanotube/TiO 2 that performed a greater sensitivity with an LOD of 0.003 μM of RhB; however, our fabricated sensor’s electrode is still possible to be applied in detecting the presence of RhB in food samples as well.…”
Section: Resultsmentioning
confidence: 86%
“…As far as we know, only one SPCE modification for the detection of RhB has been reported. 24 Graphene is a monolayer material composed of carbon atoms with an sp 2 bond and π orbital. Graphene is a one-atomthick two-dimensional hexagonal lattice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents a comparison of the RhB sensing performance of our designed sensor with reported sensors. [39][40][41][42][43][44][45][46][47][48][49][50] Hence, GCE modied with functionalized multiwalled carbon nanotubes is a promising tool for the trace level detection of Rhodamine B dye.…”
Section: Analytical Characterizationmentioning
confidence: 99%
“…Rhodamine B has been studied at a number of different electrode materials [28][29][30][31][32][33][34][35]. However, it is believed that this study represents the first report on the voltammetric behaviour and determination of Rhodamine B in an environmental water sample at an unmodified SPCE.…”
Section: Introductionmentioning
confidence: 99%